Simulations of Cold Electroweak Baryogenesis: quench from portal coupling to new singlet field - Mou, Zong-Gang; Saffin, Paul M.; Tranberg, Anders (Springer, 2018)
We compute the baryon asymmetry generated from Cold Electroweak Baryogenesis, when a dynamical Beyond-the-Standard-Model scalar singlet field triggers the spinodal transition. Using a simple potential for this additional field, we match the speed of the quench to earlier simulations with a "by-hand" mass flip. We find that for the parameter subspace most similar to a by-hand transition, the final baryon asymmetry shows a similar dependence on quench time and is of the same magnitude. For more general parameter choices the Higgs-singlet dynamics can be very complicated, resulting in an enhancement of the final baryon asymmetry. Our results validate and generalise results of simulations in the literature and open up the Cold Electroweak Baryogenesis scenario to further model building.